Investigating the Factors Contributing to the Formation of Secondary School Students' Interest towards Higher Education Studies - Athina G. Mitsopoulou; Evangelia A. Pavlatou (MDPI AG, 2024)
The present study's objective constitutes the examination of the prognostic factors that influence the inclination of students in secondary school towards pursuing higher education. To achieve this goal, an existing questionnaire was utilized and appropriately altered to align with the Greek educational system. The survey involved the participation of 301 secondary school students from Piraeus, which comprises one of Greece's major cities. The outcomes of the research yield substantial endorsement for the principles outlined in the social cognitive career theory. Specifically, the study highlights the significant role of family background, encompassing the educational levels of the parents, the students' perceptions of the family's financial situation, and the financial support provided by the family during the students' academic journey, in shaping the students' intent towards pursuing higher education. Moreover, the presence of a secure attachment bond between students and their parents suggests a favorable inclination towards higher education. Conversely, students deriving from low-income families are prone to exhibit hesitancy in pursuing higher education. The acquired data reveal a constructive relationship among outcome expectations, social support, as well as the process of students' interest in developing a desire for higher education. Conversely, factors such as gender and age, as well as the presence of siblings studying in higher education, appear to have little influence in this regard.